Suplementação alimentar de abelhas africanizadas (apis mellifera l.) na região do semiárido - Sombra, Daiana da Silva (2018)
The lack of pollen in nature during the period of scarcity in the semi-arid region affects the productivity of the colonies, thus, the objective of this work was to develop and test artificial protein diets for colonies of Apis mellifera bees, using leucena (Leucaena leucocephala) and macroalgae Gracilaria birdiae. For the laboratory tests, bees in confinement cages were fed for seven days with different diets: D1 (Beebread and candy (sugar with honey)), D2 (Megabee® - commercial diet), D3 (50% sucrose syrup (v / v)), D4 and D5 (corn bran, soybean meal and leucena as main ingredients with different concentrations) D6 (corn bran and soybean meal), D7 (corn bran and leucena), D8 (corn bran and crystal sugar) and D9 (Promoter L®). Collection of hemolymph samples from worker bees were collected for analysis of protein concentration. Two experiments were carried out in the field: 1) test of diets selected by the result of protein concentration in hemolymph (D5, D6 and 50% sucrose syrup (v / v)); and 2) evaluation of diets based on macroalgae G. birdiae (EA - algal extract with 50% sucrose syrup (v / v), M + S – soybean meal, corn bran and 50% sucrose syrup ( v / v), M + FA - algae meal, corn bran and – 50% sucrose syrup (v / v); control- 50% sucrose syrup (v / v)). In both field experiments, the consumption of pasty diets, weight gain of colonies and the percentage of area occupied in combs with posture, brewed and open breeding, pollen, honey and open nectar were measured. In experiment 1 there was no difference in diets consumption or colony weight gain, but there was a higher percentage of area occupied with eggs in the colonies fed with the D5 diet, being statistically higher than the average of the group that received the D6 diet. The D5 diet was also significantly higher for the area of brood and open breeding. In the experiment 2, the consumption of the M + FA diet was superior to the M + S diet, but no difference in the weight of the colonies of any treatment occurred. The percentage of area occupied in the combs presented statistical difference only for the honey variable, where the diet M + FA was superior to the control and EA, but not differing from M + FA. Based on these results we can suggest that the inclusion of leucena and the macroalgae G. birdiae in the diet of the bees, suits as a substitute for pollen. Because they are regional and low cost products found in abundance along the Brazilian Northeast coast, they are considered accessible to beekeepers and are therefore excellent alternatives for bee protein feeding during the period of food scarcity in the northeastern semi-arid region